(3HSJGf GdYGQajfs - (3GdSeQbfOj, CHh GddjK, EeGe GdgOi, fUQ Hf eMeO Hf CMeO Hf EHQGgje, (B373 (3g`s
(3ChdgG (B:s
(3bO LeYJ aj cJGHj gPG afhf ef GdYde eG dG jSY LgdghSejJg cJGH GdHSJGfs
(3BNQgG (B:s
(3cGf ef GdJChjd GdChd aGdCTHg Cf dG jecfge GdhUhd Edi QGOg hEf cGf bO jLhR aj GdMce Cf jWdYge Ydjg SHMGfg ef dWag Cfg gh GddWja GdNHjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 8 / 27s
(3eYLe GdeDdajf(B: 4 / 24s
(3cTa GdXfhf(B: 1 / 243s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs